Efisiensi Distribusi Bawang Goreng dan Tepung Bakso: Pendekatan Metode Least Cost dan Stepping Stone - Fendiyanto, Petrus; Kurniawan, Kurniawan (Griya Journal of Mathematics Education and Application, 2025)
This study aims to optimize the distribution costs of processed food products, specifically fried shallots and meatball flour packages, from two distribution agents of UD. Berkah Mandiri to three main markets in Samarinda City. The method used is a linear transportation model with the Least Cost and Stepping Stone approaches, validated using LINGO software. The results show that distribution costs can be reduced from Rp 3.387.506 to Rp 1.877.340, achieving a cost efficiency of 44.6%. Validation using LINGO confirmed identical results, reinforcing the accuracy of the applied methods. These findings indicate that optimization-based mathematical approaches are highly relevant for UMKM to improve logistics efficiency, especially in the distribution of processed products such as fried shallots and meatball flour.